2017
DOI: 10.1097/aog.0000000000001995
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Vaginal Hysterectomy Techniques and Interventions for Benign Indications

Abstract: Minimal data exist to guide surgeons with respect to planning and performing a vaginal hysterectomy. This study identifies available information and future areas for investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 62 publications
2
27
0
Order By: Relevance
“…A recent systematic review that has identified 15 studies and involved a total of 1389 patients has noted that the use of tissue sealer devices is associated (moderate level of evidence) with decreased operative time and blood loss in VH compared with traditional suture ligation [20]. The incorporation of use of the vessel-sealing device with the round ligament technique has been previously described for vaginal salpingectomy [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review that has identified 15 studies and involved a total of 1389 patients has noted that the use of tissue sealer devices is associated (moderate level of evidence) with decreased operative time and blood loss in VH compared with traditional suture ligation [20]. The incorporation of use of the vessel-sealing device with the round ligament technique has been previously described for vaginal salpingectomy [25].…”
Section: Discussionmentioning
confidence: 99%
“…Traditional RCs to VH are identified based on expert opinion and include obesity (≥class I), nulliparity, previous cesarean delivery, presence of adhesions from previous surgery, enlarged uterus, lack of prolapse, and presence of benign adnexal pathologic condition [20,21]. Studies that examined patient characteristics that were traditionally considered to be barriers to VH failed to show a difference in observed length of hospital stay or increased risk of complications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review examining perioperative risk factors for VH, concurrent bilateral salpingo-oophorectomy was reported as a risk factor for complications [14]. In another study evaluating salpingo-oophorectomy by the transvaginal route, 127 patients (109 patients with concurrent VH and 18 patients with previous VH) had transvaginal salpingo-oophorectomy, and it was found that complications developed in 9 of the 109 patients (fever, bleeding, ureteral injury, return to operating theatre) [15].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have argued that a history of previous pelvic surgery is not an obstacle for VH and does not increase complication rates [19,21]. Conversely, the study of Akyol et al [10] and the review of Jeppson et al [14] reported that a history of previous pelvic surgery was associated with development of complications in VH. In this study, it was found that a history of previous pelvic surgery was statistically higher in the group with complications.…”
Section: Discussionmentioning
confidence: 99%